Lentiviral Vectors Displaying Modified Measles Virus gp Overcome Pre-existing Immunity in In Vivo-like Transduction of Human T and B Cells - Lévy, Camille (Nature Publishing Group, 2012)
Gene transfer into quiescent T and B cells is important for gene therapy and immunotherapy approaches. Previously, we generated lentiviral vectors (LVs) pseudotyped with Edmonston (Ed) measles virus (MV) hemagglutinin (H) and fusion (F) glycoproteins (H/F-LVs), which allowed efficient transduction of quiescent human T and B cells. However, a major obstacle in the use of H/F-LVs in vivo is that most of the human population is vaccinated against measles. As the MV humoral immune response is exclusively directed against the H protein of MV, we mutated the two dominant epitopes in H, Noose, and NE. LVs pseudotyped with these mutant H-glycoproteins escaped inactivation by monoclonal antibodies (mAbs) but were still neutralized by human serum. Consequently, we took advantage of newly emerged MV-D genotypes that were less sensitive to MV vaccination due to a different glycosylation pattern. The mutation responsible was introduced into the H/F-LVs, already mutated for Noose and NE epitopes. We found that these mutant H/F-LVs could efficiently transduce quiescent lymphocytes in the presence of high concentrations of MV antibody-positive human serum. Finally, upon incubation with total blood, mimicking the in vivo situation, the mutant H/F-LVs escaped MV antibody neutralization, where the original H/F-LVs failed. Thus, these novel H/F-LVs offer perspectives for in vivo lymphocyte-based gene therapy and immunotherapy.